Green marketing as an environmental practice: The impact on green satisfaction and green loyalty in a business‐to‐business context. (25th January 2021) - Gelderman, Cees J.; Schijns, Jos; Lambrechts, Wim; Vijgen, Simon
Abstract: Many companies have developed a green marketing strategy, aimed at promoting and selling green environmental products. While the majority of articles on this topic report on studies in a business‐to‐consumer setting, this research focusses on the impact of green marketing strategies on the satisfaction and loyalty of professional buyers in a business‐to‐business setting. Hypotheses were tested with survey data from 148 Dutch professional purchasers in the cleaning industry. The results emphasize the impact and importance of product quality, product price and corporate image. The most notable and strong impact on satisfaction and loyalty was found for the salesperson expertise.